Room-temperature multiferroic behaviour in Co/Fe co-substituted layer-structured Aurivillius phase ceramics. Issue 20 (15th October 2022) - Alkathy, Mahmoud S.; Rahman, Attaur; Zabotto, Fabio L.; Milton, Flavio Paulo; Raju, K.C. James; Eiras, J.A.
Abstract: Room-temperature single-phase multiferroic materials have attracted the considerable attention of may scientists due to their technological applications in the next-generation electronic devices. Here, we report the structural evolution and its relationship with the ferroelectric and magnetic properties of Aurivillius Bi3.25 Sm0.75 Ti(3-x) ( Fe, Co)x O12 (BSmT:FCx); for (0≤x ≤ 0.4) ceramics to elucidate the room-temperature multiferroics induced by Fe/Co co-substitution. The XRD analysis and structural refinements reveal that incorporating of Co, and Fe ions into Ti sites of BSmT host lattices gives rise to a single orthorhombic phase with no evidence of secondary phases. The X-ray photoelectron spectroscopy (XPS) spectra indicate the existence of oxygen vacancies in the investigated samples. Pure BiT samples exhibit diamagnetic behavior, while BSmT:FCx; for (0≤x ≤ 0.4) exhibits ferromagnetic behavior at room temperature. As a result, the sample with x = 0.4 displayed the highest remnant and saturation magnetization values. It is believed that the occurrence of magnetism causes by the magnetic double exchange interaction between the non-equivalent magnetic ions and oxygen. The reversible polarization induced by an electric field indicates the ferroelectric character of the ceramics at room temperature. The co-substituting samples show unsaturated P-E hysteresis loops, which could be caused by the domain pinning induced by the accumulation of oxygen vacancies near the domain boundaries. We expect these compounds are promising for developing electronic devices for future applications.